2010
DOI: 10.1007/s12664-010-0074-4
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the double-barreled wet colostomy for simultaneous urinary and fecal diversion—an Indian experience

Abstract: Pelvic exenteration in advanced malignancies is usually a curative procedure aimed at improving quality of life. We analyzed the perioperative data and outcomes in 12 patients who underwent simultaneous urinary and fecal diversion with a double-barreled wet colostomy after total pelvic exenteration. Eight males and four females aged between 25 and 73 years underwent the procedure with mean operative duration of 350 min and mean postoperative stay of 15 days. Three patients developed early complications while f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 10 publications
(12 reference statements)
1
11
0
Order By: Relevance
“…In the group of patients analyzed in this series, almost all but one patient were operated for colorectal adenocarcinomas, just one with a prostate neuroendocrine tumor. We have found that it is a safe procedure even in patients 70 years old or older, as other authors that have performed the procedure in patients in the eight decade of life with good perioperative results [ 2 , 13 15 ] ( Table 1 ).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In the group of patients analyzed in this series, almost all but one patient were operated for colorectal adenocarcinomas, just one with a prostate neuroendocrine tumor. We have found that it is a safe procedure even in patients 70 years old or older, as other authors that have performed the procedure in patients in the eight decade of life with good perioperative results [ 2 , 13 15 ] ( Table 1 ).…”
Section: Discussionsupporting
confidence: 68%
“…Urinary stones have been reported in the colonic urinary reservoir. Other early complications with lower incidence are the ones associated with the perineal wound, postoperative ileus, and central venous access infection [ 2 , 3 , 10 , 13 15 ]. Only Carter has reported the presence of a metabolic acidosis associated with the urinary reservoir, complication that can be seen in any patient with an intestinal urinary reservoir [ 8 , 10 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 DBWC is used in pelvic exenteration for gynecologic, urologic or colorectal cancer. 2,3,[8][9][10][11][12][13][14] Large groups have demonstrated the safety of this surgery and are even extending the age limit, doing surgery on octogenarian patients. 2,[9][10][11][12][13][14] Several complications have been associated to urinary diversion.…”
Section: Discussionmentioning
confidence: 99%
“…Perineal wound infection, post-operative ileus, vascular access infection, among other complications have been reported in this type of procedure. 2,3,9,[12][13][14] Metabolic acidosis is another possible complication in patients with a urinary reservoir. 7,9,16 Perioperative mortality for this type of surgery is reported from 0% to 11.56%.…”
Section: Discussionmentioning
confidence: 99%